Identification and genomic analyses of a novel endophytic actinobacterium Streptomyces endophytica sp. nov. with potential for biocontrol of yam anthracnose - Zhou, Shuangqing; Zhou, Yifan; Li, Chengui; Wu, Wenqiang; Xu, Yun; Xia, Wei; Huang, Dongyi; Huang, Xiaolong (Frontiers in Microbiology, 2023)
Anthracnose disease caused by Colletotrichum gloeosporioides is one of the devastating diseases of yams (Dioscorea sp.) worldwide. In this study, one hundred sixteen endophytic actinomycete strains were isolated from the surface-sterilized yam tissues from yam orchard in Hainan, China. Twenty-three isolates showed antagonistic activity against C. gloeosporioides. An endophytic actinomycete, designated HNM0140T, that exhibited strong antifungal activities, multiple biocontrol and plant growth-promoting (PGP) traits was subsequently selected to colonize in the tissue-cultured seedlings of yam and was tested for its in vivo biocontrol potential on yam anthracnose. Results showed that treatment with strain HNM0140T markedly reduced the severity and incidence of yam anthracnose under greenhouse conditions. Morphological and chemotaxonomical analysis showed that strain HNM0140T assigned to the Streptomyces genus. Phylogenetic analysis based on 16S rRNA gene sequences indicated strain HNM0140T formed a separate branch together with Streptomyces lydicus ATCC 25470T(99.45%), Streptomyces chattanoogensis NRRL ISP-5002T(99.45%) and Streptomyces kronopolitis NEAU-ML8T(98.97%). The phylogenomic tree reconstructed on TYGS also showed that strain HNM0140T stably clustered with Streptomyces lydicus ATCC 25470T. The ANI and dDDH between strain HNM0140T and its closest related type species were well below the recommended thresholds for species demarcation. Hence, Based on phylogenetic, genomic and phenotypic analysis, strain HNM0140T should represent a new streptomycete species named Streptomyces endophytica sp. nov. The complete genome size of strain HNM0140T was 6.9 Mbp with G+C content of 72.2 mol%. Genomic analysis revealed that strain HNM0140T harbored eighteen putative BGCs for secondary metabolites, some PGP related genes and several genes coding for antifungal enzymes. The present results indicated that strain HNM0140T was a promising biocontrol agent for yam anthracnose.